Think green, take action : books and activities for kids - Kriesberg, Daniel A.; Price, Kathleen A. (Santa Barbara, Calif. : Libraries Unlimited, 2010)
Contains an annotated bibliography of books that teach third- through seventh-grade students about environmental issues, and suggests related classroom activities.
Why and how to teach green -- Understanding the ecology ofyour home place -- Endangered species -- Resource depletion -- Pollution -- Activities for action.
Includes bibliographical references and index.
Professional
Professional
Keywords: Environmental education -- Activity programs; Environmental sciences -- Juvenile literature -- Bibliography; Environmental sciences -- Study and teaching (Elementary); Environmental sciences -- Study and teaching (Elementary) -- Activity programs; Environmental education; Environmental sciences -- Juvenile literature -- Bibliography; Environmental sciences -- Study and teaching